Parental effects on carotenoid-based plumage coloration in nestling great tits, Parus major - Isaksson, C; Uller, T; Andersson, S (2006)
Carotenoid pigments have attracted much interest in behavioural and evolutionary ecology because of their dual function in immune physiology and as color signals. In vertebrates, carotenoids must ultimately be obtained from the diet, and the mechanisms and magnitude of this environmental dependence are central for understanding carotenoid signal functions and evolution. In the present cross-fostering experiment with great tits Parus major, we investigate pre- and postnatal parental effects (egg yolk carotenoids, parental coloration) on nestling size and carotenoid coloration, using HPLC analysis of egg yolk carotenoids, and a reflectance-based measure of 'chroma' that reflects the plumage pigment concentration. Both rearing environment and origin influenced offspring size and plumage chroma. Maternal allocation of carotenoids to eggs had a weak positive effect on nestling plumage chroma, whereas we found no prenatal maternal effects (egg size or yolk carotenoid concentration) on size. Nestling plumage chroma was also significantly predicted by the chroma of the rearing father, but not by the color of the rearing mother or either of the original (genetical) parents. Thus, both prenatal maternal effects and postnatal paternal effects influence the carotenoid-based plumage coloration of nestling great tits. Future studies will reveal if parental effects have long-term consequences for plumage development and associated fitness components. © Springer-Verlag 2006.